An international experience with single-operator cholangiopancreatoscopy in patients with altered anatomy - Mony, Shruti; Ghandour, Bachir; Raijman, Isaac; Manvar, Amar; Ho, Sammy; Trindade, Arvind J.; Benias, Petros C.; Zulli, Claudio; Jacques, Jérémie; Ichkhanian, Yervant; Zuchelli, Tobias; Ghanimeh, Mouhanna Abu; Irani, Shayan; Canakis, Andrew; Sanaei, Omid; Szvarca, Daniel; Zhang, Linda; Bejjani, Michael; Akshintala, Venkata; Khashab, Mouen A. (Endoscopy International Open, 2022)
Background and study aims The utility of digital single- operator cholangiopancreatoscopy (D-SOCP) in surgically altered anatomy (SAA) is limited. We aimed to evaluate the technical success and safety of D-SOCP in patients SAA.Patients and methods Patients with SAA who underwent D-SOCP between February 2015 and June 2020 were retrospectively evaluated. Technical success was defined as completing the intended procedure with the use of D-SOCP.Results Thirty-five patients underwent D-SOCP (34 D-SOC, 1 D-SOP). Bilroth II was the most common type of SAA (45.7 %), followed by Whipple reconstruction (31.4 %). Twenty-three patients (65.7 %) patients had prior failed ERCP due to the presence of complex biliary stone (52.2 %). A therapeutic duodenoscope was utilized in the majority of the cases (68.6 %), while a therapeutic gastroscope (22.7 %) or adult colonoscope (8.5 %) were used in the remaining procedures. Choledocholithiasis (61.2 %) and pancreatic duct calculi (3.2 %) were the most common indications for D-SOCP. Technical success was achieved in all 35 patients (100 %) and majority (91.4 %) requiring a single session. Complex interventions included electrohydraulic or laser lithotripsy, biliary or pancreatic stent placement, stricture dilation, and target tissue biopsies. Two mild adverse events occurred (pancreatitis and transient bacteremia).Conclusions In SAA, D-SOCP is a safe and effective modality to diagnose and treat complex pancreatobiliary disorders, especially in cases where standard ERCP attempts may fail.